Ligation of Processus Vaginalis During Orchidopexy: Is It Mandatory? - Khan, Feeroz Alam; Maharjan, Prabir (Journal of Nepalgunj Medical College, 2022)
Introduction: Undescended testis is one of the commonest presentations in pediatric population. Conventionally, high ligation of the hernia sac was done after vas and vessels were dissected in order to prevent post-operative hernia. However, recent studies have shown that hernia sac ligation was unnecessary.Aims: To evaluate the role of hernia sac ligation during orchidopexy to prevent the development of postoperative hernia and to compare the mean operative time with and without sac ligation.Methods: A prospective comparative study was conducted with a total of 94 patients with undescended testis, age ranging from six months to 16 years were included in the study from November 2018 to May 2021. Cases were randomly divided into two groups. In Group A cases, orchidopexy was carried out with sac ligation, while in Group B, the hernia sac was not ligated. Mean operative time was recorded in each case. All the patients were followed up at one, four and eight weeks post-operatively and examined for postoperative hernia.Results: Of the total 94 cases, there were 18 bilateral and 76 unilateral cases of which 56 were right-sided and 22 left-sided. Most of the patients (45) of the study were between six months and 2 years. None of the patients of either group developed post-operative hernia or any significant complications. The mean operative time for group A and B were 36.72 and 46.96 minutes respectively.Conclusion: It was concluded that ligation of processus vaginalis was unnecessary during orchidopexy and sac ligation consumed more operative time.